Paleogene stratigraphy in the central area of the Fuegian fold and thrust belt, Austral Basin, Argentina: Implications for the chronology of thrust-belt deformation - Gutierrez, Cecilia Inés (2024)
We combine extensive field data with calcareous nannofossils and dinocysts analysis and detrital zircon U-Pb ages to identify six Paleocene-Oligocene stratigraphic units in a previously poorly studied area in the external fold and thrust belt of the Fuegian Andes. Detailed petrographic analysis coupled with detrital zircon ages indicate three main provenance peaks, which reflect that 1) the lowermost upper Cretaceous was already exhumed during the Paleocene-early Eocene, 2) the upper Cretaceous rocks were a continuous source at least until the late Eocene, 3) volcanism was coetaneous with the deposition of middle Eocene successions. Three contractional stages known elsewhere in the thrust-belt are identified in the study area in the Danian, the early Eocene-early middle Eocene, and the latest Eocene-early Oligocene. This suggests synchronicity along strike during the evolution of the Fuegian fold and thrust belt.